PENERAPAN MODEL PEMBELAJARAN BASED LEARNING (PBL) UNTUK MENINGKATKAN PEMAHAMAN SISWA KELAS IV PADA MATERI PENJUMLAHAN PECAHAN DI SEKOLAH DASAR NEGERI 3 CILEULEUY - Aef Ivan Rivana; Siti Sholiha Nurfaidah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2022)
This research was motivated by the low mathematical understanding of the fourth grade students of SDN 3 Cileuleuy on the matter of adding fractions. Based on the results of observations, only 3 students out of 11 students obtained test scores above/equal to the KKM 70. So this study aims to improve students' mathematical understanding of fraction addition material in class IV SDN 3 Cileuleuy through the use of Model Pembelajaran Based Learning (PBL) models. The research method used is Classroom Action Research (CAR). The research design consisted of 2 cycles where the research subjects were 11 students of class IV SDN 3 Cileuleuy consisting of 8 male students and 3 female students. Data collection techniques were carried out through tests (evaluation tests) and non-tests (observations and documentation). The data analysis technique used is descriptive quantitative to analyze the results of evaluation tests and qualitative descriptive analysis to analyze the results of student evaluations. The results showed that there was an increase in students' mathematical understanding from before giving the action until the second cycle. Individual completeness before giving the action is 3 students with classical completeness reaching 27% and the average value obtained is 63.18. Then in the first cycle, 7 students obtained individual mastery with an average value of 70.27 and classical learning completeness of 63%. In the second cycle, individual mastery increased to 10 students with an average value of 81.89 and classical learning completeness increased to 85%. Based on the results obtained, it can be concluded that the use of the Problem Based Learning (PBL) model can improve students' mathematical understanding of ordinary fractions in the fifth grade of SDN 3 Cileuleuy in the 2022/2023 academic year.